Clinical, biochemical and haemathological effects in Rhamdia quelen exposed to cypermethrin - Montanha, Francisco Pizzolato; Fredianelli, Ana Carolina; Wagner, R.; Sacco, Soraya Regina [UNESP]; Rocha, Daniel Carlos Coatti; Pimpão, Cláudia Turra (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The acute intoxication of Cypermethrin in Silver Catfish (Rhamdia quelen) was evaluated. Animals weighing 56.67±4.43g and measuring 18.92±1.16cm were exposed to sublethal concentrations of Cypermethrin for the species in hydrological conditions during 96 hours. A total of 52 fish divided into three groups were used and received the following concentrations of Cypermethrin: 0 (n=12); 1.5 (n=20) and 2.5 (n=20)mg/L. The intoxicated animals suffered behavioral changes such as loss of balance, swimming alteration, dyspnea, upright swimming and sudden spiral swimming movements. As soon as the 96-hour period was over, a blood collection for hematological and biochemical analyses was performed. A complete haemogram test, plasmatic protein test, albumin, alanine transaminase (ALT), aspartate aminotransferase (AST), gamma glutamyltransferase and alkaline phosphatase (ALP) were studied. The values of erythrocytes, hematocrits, haemoglobin, total number of leukocytes, thrombocyte, ALT, AST and ALP changed according to the groups. The results have shown that the environmental contamination by Cypermethrin is toxic to the species.

Avaliou-se a intoxicação aguda da cipermetrina em jundiás (Rhamdia quelen). Jundiás que pesavam 56,67±4.43g e mediam 18,92±1,16cm foram expostos a concentrações subletais de cipermetrina para a espécie em 96 horas, via hídrica, utilizando-se 52 peixes, distribuídos em três grupos, segundo a concentração de cipermetrina: 0 (n = 12); 1,5 (n = 20) e 2,5 (n = 20)mg/L. Os animais intoxicados apresentaram alterações comportamentais, como perda de equilíbrio, dispneia, natação na posição vertical e movimentos bruscos de natação em espiral. Após 96 horas de exposição, foi coletado sangue para análises de hemograma completo, proteína plasmática, albumina, alanina aminotransferase (ALT), aspartato aminotransferase (AST), fosfatase alcalina (ALP) e gamaglutamiltransferase. Os valores de eritrócitos, hematócrito, hemoglobina, número total de leucócitos, número total de plaquetas, ALT, AST e ALP diferiram entre os grupos. Os resultados demonstraram que a contaminação ambiental por cipermetrina é tóxica para a espécie.
Efeitos clínicos, bioquímicos e hematológicos em Rhamdia quelen expostos à cipermetrina
Keywords: Peixe; Biomarcadores; Ecotoxicologia; Hemograma; Piretroides; Fish; Biomarkers; Ecotoxicology; Haemogram; Pyrethroids